Peran Komunikasi Pendidikan Sebagai Kesatuan Dalam Pembelajaran - I Nyoman Sueca (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
Communication education has a quite important position both in terms of scientific communication and from the scientific side of education. In terms of scientific communication, the study of educational communication will enrich and expand the field of communication science studies, more than the coverage that has existed so far. The existence of a study of education communication as a science itself does indeed still need in-depth testing, especially related to the aspects of ontology, epistemology, and its axiology. Education is a noble agenda in all countries because through State education will be able to prepare the young generation who have a sense of nationalism and patriotism and have the ability to survive and compete in global relations. Education is the most appropriate way to continue and pass on the noble values ​​that become the identity and personality of the nation and cultural inheritance (The transmitting of social culture) from one generation to the next. Communication as the process of sending and receiving messages is a form of transferring information. A teacher who acts as the sender of the message will convey the message to the students. The messages received by students are then developed and continued and elaborated in person and in pairs and in groups. The response given by students becomes a note for the teacher including the critical questions of the students which require the teacher to find new information. If this process occurs in learning then communication plays a function as the development of knowledge not only for students but also educators themselves.